2003
DOI: 10.1111/j.1572-0241.2003.07702.x
|View full text |Cite
|
Sign up to set email alerts
|

Response To Treatment of Hepatitis C in Individuals With A Recent History of Intravenous Drug Abuse

Abstract: The SR rate achieved by intravenous drug abusers to high-dose, daily IFN is similar to that in a non-drug-abusing HCV positive population. Recent use of illicit drugs within a 6-month period of starting IFN therapy or continued methadone use during treatment does not seem to impair the response to IFN when the results are compared with those of a matched cohort of non-drug-abusing controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Although some authors have identified increased depression score at baseline as a risk factor for higher depression score during treatment with standard IFN-␣, our data are in line with the results of other controlled trials that did not find differences in changes in depression scores during IFN-␣ treatment between patients with preexisting depression and nonpsychiatric controls. 17,[27][28][29][30][31] One possible explanation for the higher increase in depression scores in the control group might be the smaller number of patients who received antidepressants before antiviral therapy was started. In fact, recent data showed that at least for preexisting depressive symptoms, preemptive treatment with citalopram can decrease the incidence of major depressive episodes during treatment of chronic hepatitis C with pegIFN-␣-2b and ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have identified increased depression score at baseline as a risk factor for higher depression score during treatment with standard IFN-␣, our data are in line with the results of other controlled trials that did not find differences in changes in depression scores during IFN-␣ treatment between patients with preexisting depression and nonpsychiatric controls. 17,[27][28][29][30][31] One possible explanation for the higher increase in depression scores in the control group might be the smaller number of patients who received antidepressants before antiviral therapy was started. In fact, recent data showed that at least for preexisting depressive symptoms, preemptive treatment with citalopram can decrease the incidence of major depressive episodes during treatment of chronic hepatitis C with pegIFN-␣-2b and ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…Although past treatment options have been relatively ineffective, new treatment advances have substantially improved outcomes (Fried et al, 2002;Manns et al, 2001). A growing number of studies now provide evidence for the efficacy of interferon-based therapy for HCV-infected patients with active substance abuse disorders (Backmund, Meyer, Von Zielonka, & Eichenlaub, 2001;Cournot et al, 2004;Dalgard et al, 2002;Sylvestre, Litwin, Clements, & Gourevitch, 2005;Van Thiel, Anantharaju, & Creech, 2003). However, despite the high prevalence of HCV infection among IDUs, few have been treated with interferon-based antiviral therapy Hagan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, injection drug users respond to HCV treatment in a fashion similar to those without a history of substance abuse. 14,15 Interim data from a recent study suggest that treatment of HCVinfected individuals utilizing methadone maintenance for the control of opioid addiction is as effective as treatment for non-drug users with HCV infection, although general management issues are more difficult to handle. 16 Currently, treatment recommendations for individuals on methadone maintenance therapy, endorsed by the American Association for the Study of Liver Disease and the Infectious Diseases Society of America, 17 state that the use of methadone does not preclude medical management of hepatitis C. However, it must be noted that patients on methadone maintenance therapy may have difficulty in completing interferon-based therapy regimens.…”
Section: Hcv Care and Treatment And Injection Drug Usementioning
confidence: 99%